Epigenetic and epitranscriptomic regulation during oncogenic γ-herpesvirus infection - Singh, Rajnish Kumar; Vangala, Ramakrishna; Torne, Atharva S.; Bose, Dipayan; Robertson, Erle S. (Frontiers in Microbiology, 2025)
Oncogenic gamma herpesviruses, including Epstein–Barr Virus (EBV) and Kaposi’s Sarcoma-associated Herpesvirus (KSHV), are opportunistic cancer-causing viruses and induces oncogenesis through complex mechanisms, which involves manipulation of cellular physiology as well as epigenetic and epitranscriptomic reprogramming. In this review, we describe the intricate processes by which these viruses interact with the epigenetic machinery, leading to alterations in DNA methylation, histone modifications, and the involvement of non-coding RNAs. The key viral proteins such as EBNA1 and LMP1 encoded by EBV; LANA and vGPCR encoded by KSHV; play pivotal roles in these modifications by interacting with host factors, and dysregulating signaling pathways. The resultant reprogramming can lead to activation of oncogenes, silencing of tumor suppressor genes, and evasion of the immune response, which ultimately contributes to the oncogenic potential of these viruses. Furthermore, in this review, we explore current therapeutic strategies targeting these epigenetic alterations and discuss future directions for research and treatment. Through this comprehensive examination of the epigenetic and epitranscriptomic reprogramming mechanisms employed by oncogenic gamma herpesviruses, we aim to provide valuable insights into potential avenues for novel therapeutic interventions.